SP8.1.4 Design features of the EPR-integrated Southampton Breast Cancer Data System (SBCDS), with timeline structured whole-of-life records on 20, 000 sequential cases since the 1970s. (28th October 2021) - Rahman, Fatima; Hales, Alan; Cable, David; Rew, David
Abstract: Introduction: The digitisation of the electronic patient record (EPR) provides transformative opportunities for data visualisation. The synchronised timeline and iconographic interface permits the whole-of-life display, navigation and interpretation of all documents and reports of each and every EPR on a single screen, thus substantially facilitating clinical research. Methods: Since 2010, we have conceived, programmed and iterated a radical interface, UHS Lifelines, within our Trust EPR using agile methodology. It is live for >2.5M record sets, and enriched with cellular pathology records back to 1990. We have integrated this interface into a unique, HTML-enabled, dynamic and continually updated database for the recording of treatments and pathologies of all cases of breast neoplasia from our current and historic record sets. Results: As of January 2021, our data system contains ∼20, 000 sequential whole of life records of patients with breast neoplasia, including ∼15, 000 locally diagnosed and ∼ 5, 000 externally referred cases. The unique Cancer Lifetrack timelines displays the disease course of every case from primary diagnosis, through loco-regional recurrence, to distant metastasis, other morbid cancers and cause of death, where relevant. An integral data mining system permits a wide range of analyses. Conclusions: We believe our Breast Cancer Data System to be the first-in-class exemplar of a new and proven approach to clinical data visualisation. It permits near-instantaneous oversight and real time updating of every patient record in the system. We recognise its potential application for the whole-of-life study of all chronic diseases of childhood and adulthood as the model is more widely adopted.